2015
DOI: 10.13075/mp.5893.00144
|View full text |Cite
|
Sign up to set email alerts
|

Rescue procedures in the major trauma of upper extremities – The role of the polish medical air rescue in the therapeutic process

Abstract: StreszczenieWstęp: Ze względu na wykorzystanie różnego rodzaju maszyn przemysłowo-rolniczych wypadki w pracy należą do najpoważ-niejszych i niejednokrotnie powodują u poszkodowanego trwałe kalectwo pourazowe. W Polsce od 2010 r. działa serwis replantacyjny, co oznacza, że każdego dnia 1 z 6 ośrodków pełni dyżur replantacyjny, przyjmując z terenu całego kraju zgłoszenia dotyczące amputacji kończyn. Pacjenci zakwalifikowani do replantacji często wymagają transportu do szpitala docelowego z miejsc odległych nawet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…They found that for patients with acute coronary syndrome, the median time that passed from the receipt of the call to patient transfer to the target hospital was 81 min, and the transport distance was 59.4 km, whereas in patients with sudden injury the median time from the receipt of the call to patient transfer to the target hospital was 115 min, and the distance was 135.9 km [42]. The results of the authors' own study showed that the average time from the receipt of the call to patient transfer in the incubator to the target center was much longer and amounted to 269.16 min, while the distance during transport was also greater, that is 304.27 km, compared to the above analyses of air transports [41,42].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…They found that for patients with acute coronary syndrome, the median time that passed from the receipt of the call to patient transfer to the target hospital was 81 min, and the transport distance was 59.4 km, whereas in patients with sudden injury the median time from the receipt of the call to patient transfer to the target hospital was 115 min, and the distance was 135.9 km [42]. The results of the authors' own study showed that the average time from the receipt of the call to patient transfer in the incubator to the target center was much longer and amounted to 269.16 min, while the distance during transport was also greater, that is 304.27 km, compared to the above analyses of air transports [41,42].…”
Section: Discussionmentioning
confidence: 76%
“…The study on the contribution of the Polish Medical Air Rescue in the rescue procedure in case of severe upper limb injuries was conducted by Gałązkowski et al (2014). Their study showed that the average inter-hospital air transport time of patients with severe upper limb injuries was 75.8 min and the total transport time-172.3 min [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flights to AT patients who have suffered injuries in road or construction accident and other events resulting in lifethreatening situations are as frequent as cases of AMI. Patients fulfilling the criteria for enrollment in a trauma center (TC), a center for the treatment of burns or a hospital performing the replantation of limbs can be transported by air, which is beneficial from the point of view of saving time, minimizes the shaking present during ambulance transport 7,8 and also reduces the fatality rate. 9,10 When comparing land and aeromedical transport in the course of implementing vital procedures, an important role is played by the exceptional professional experience of HEMS teams.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this kind of arrangement, PMAR's helicopters can reach patients needing medical emergency services in the whole area of the country in an optimal time range (Fig. 2) [3,11,12].…”
Section: Structure Of Polish Medical Air Rescue (Pmar)mentioning
confidence: 99%